Unraveling Apoptosis Signalling using Linear Control Methods: Linking the Loop Gain to Reverting the Decision to Undergo Apoptosis. Issue 8 (2015) - Schliemann-Bullinger, Monica; Readman, Mark C.; Kalamatianos, Dimitrios; Findeisen, Rolf; Bullinger, Eric
Abstract: Apoptosis – programmed cell death – is a key component in cell renewal, i.e. for removing damaged cells or those not any more required without harming their environment. Understanding apoptosis is challenging since the involved signalling network is complex and intertwined. We use linear control theory to shine light on the complex signalling mechanisms and interactions. To this end we linearise different models around the steady state corresponding to the unstimulated case and use linear control analysis to uncover and identify a decentralised control scheme with two plant and two controller modules that are sparsely interconnected. While this separation on a first view is artificial, it allows for using the small gain theorem to analyse stability and to give insight into how inhibitors naturally modulate cell death. This sheds light onto the role of positive and negative feedback present in this signalling pathway. Sensitivity analysis reveals these most influential parameters on the time of death. To illustrate the analysis, we examine in simulations to which extent apoptosis can be reversed once initiated.